Antibacterial Meroterpenoids, Merochlorins G–J from the Marine Bacterium Streptomyces sp. - Min-Ji Ryu; Prima F. Hillman; Jihye Lee; Sunghoon Hwang; Eun-Young Lee; Sun-Shin Cha; Inho Yang; Dong-Chan Oh; Sang-Jip Nam; William Fenical (Marine Drugs, 2021)
Four new chlorinated meroterpenoids, merochlorins G−J (1−4), and 10, a dihydronaphthalenedione precursor, along with known merochlorins A (5) and C−F (6−9), were obtained from cultivation of the bacterium strain Streptomyces sp. CNH-189, which was isolated from marine sediment. The planar structures of compounds 1−4 and 10 were elucidated by interpretation of MS, UV, and NMR spectroscopic data. The relative configurations of compounds 1−4 were determined via analysis of nuclear Overhauser effect (NOE) spectroscopic data, after which their absolute configurations were established by comparing the experimental electronic circular dichroism (ECD) spectra of compounds 1−4 to those of previously reported possible enantiomer models and DP4 calculations. Compound 3 displayed strong antibacterial activities against Bacillus subtilis, Kocuria rhizophila, and Staphylococcus aureus, with MIC values of 1, 2, and 2 μg/mL, respectively, whereas compound 1 exhibited weak antibacterial effects on these three strains, with a 16−32 μg/mL MIC value range.